2009
DOI: 10.1002/jcb.22325
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition activates the mitochondrial pathway of apoptosis in human CD4+ T cells

Abstract: We have previously shown that inhibition of the proteolytic activity of the proteasome induces apoptosis and suppresses essential functions of activated human CD4(+) T cells, and we report now the detailed mechanisms of apoptosis following proteasome inhibition in these cells. Here we show that proteasome inhibition by bortezomib activates the mitochondrial pathway of apoptosis in activated CD4(+) T cells by disrupting the equilibrium of pro-apoptotic and anti-apoptotic proteins at the outer mitochondrial memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…This result was reported for several cell lines and multiple of proteasome inhibitors, including bortezomib [87][88][89][90][91][92], MG132 [93][94][95], lactacystin [95][96][97], aLLN [95], MG262 [95], carbobenzoxyLeu-Leu-Leu-aldehyde [97] and N-benzyloxycarbonyl-IleGlu (O-t-butyl)-Ala-leucinal [98]. ROS generation by proteasome inhibitors induces c-Jun N-terminal kinase (JNK) [92] and activator protein-1 (AP-1) activation [95], loss of mitochondrial membrane potential ( m) [87, 91-94, 97, 98], cytochrome-c release [87, 90-92, 97, 98], caspase-3 activation [87][88][89][90][91][92][93]97] and subsequent apoptosis. Similar events (e.g., JNK and AP-1 activation, decreased m and caspase-3 activation) were observed in cells treated with mixtures of EtDTC-Cu(II) [23] or PyDTC-Cu(II) [24].…”
Section: Proteasome and Oxidative Stresssupporting
confidence: 67%
“…This result was reported for several cell lines and multiple of proteasome inhibitors, including bortezomib [87][88][89][90][91][92], MG132 [93][94][95], lactacystin [95][96][97], aLLN [95], MG262 [95], carbobenzoxyLeu-Leu-Leu-aldehyde [97] and N-benzyloxycarbonyl-IleGlu (O-t-butyl)-Ala-leucinal [98]. ROS generation by proteasome inhibitors induces c-Jun N-terminal kinase (JNK) [92] and activator protein-1 (AP-1) activation [95], loss of mitochondrial membrane potential ( m) [87, 91-94, 97, 98], cytochrome-c release [87, 90-92, 97, 98], caspase-3 activation [87][88][89][90][91][92][93]97] and subsequent apoptosis. Similar events (e.g., JNK and AP-1 activation, decreased m and caspase-3 activation) were observed in cells treated with mixtures of EtDTC-Cu(II) [23] or PyDTC-Cu(II) [24].…”
Section: Proteasome and Oxidative Stresssupporting
confidence: 67%
“…We can, thus, expect therapeutic effects of bortezomib in the setting of IEX-1 overexpression in CTCL patients. Moreover, it has been recently shown that bortezomib activates the mitochondrial pathway of apoptosis in activated CD4 + T cells by altering the equilibrium of proapoptotic and antiapoptotic proteins at the outer mitochondrial membrane and by inducing ROS production [65]. Possible involvement of IEX-1 in bortezomib-induced therapeutics merits further investigation.…”
Section: Iex-1 As a Prognostic Biomarker In Cancersmentioning
confidence: 99%
“…51,52 It was further described that exposure to bortezomib led to an increased incidence of varicella-zoster infections and interferes with the priming of naive T cells. 52 Additionally, proteasome inhibition triggered the mitochondrial pathway of apoptosis by activating mutually independent apoptotic pathways 53 and suppressed essential immune functions of human CD4 þ T cells. 54 Immunomodulation by anti-angiogenic drugs A Heine et al Naturally occurring Tregs were resistant to pro-apoptotic effects of bortezomib.…”
Section: Dasatinibmentioning
confidence: 99%